벌꿀에 의한 아나필락시스 - 김지혜; 김단비; 김경훈; 이혜진; 양은애; 김환수; 전윤홍; 김현희; 김진택 (Allergy asthma & respiratory disease, 2020)
Honey is a food ingested worldwide. Allergic reaction to honey is rare and only a few cases have been reported in the literature. A 20-month-old boy developed angioedema 30 minutes after eating rice cake containing honey. After 2 weeks, we performed food challenge tests with honey which resulted in anaphylaxis. This is the first case report on anaphylaxis to honey in Korea. KCI Citation Count: 0